STRATEGI PEMBERDAYAAN DALAM MENINGKATKAN KUALITAS PENDIDIKAN ANAK USIA DINI DI PAUD AL-HIKMAH - Farina, Mahlida; Yuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the empowerment strategies implemented at PAUD Al-Hikmah to improve the quality of early childhood education services. The research employed a qualitative descriptive approach, with the subjects consisting of the principal, parents, and the head of the PAUD committee who are actively involved in the implementation of empowerment strategies, while the research objects include various forms of strategies and their contributions to improving service quality. Data were collected through semi-structured interviews, participatory observations, and documentation, including activity photos, reports, and administrative records of the PAUD. The findings indicate that the empowerment strategies at PAUD Al-Hikmah encompass equality, participation, self-reliance, and sustainability. Relationships between the school, parents, and the community are established on an equal footing through open communication, informal discussions, and joint decision-making. Parents and community members actively participate in both learning and non-learning activities, while self-reliance is manifested through voluntary support in the form of labor, ideas, and donated materials. Program sustainability is maintained through phased planning, routine evaluations, and partnerships with local businesses and health centers. These strategies strengthen the collaboration among the school, parents, and the community and contribute to improving the quality of early childhood education services at PAUD Al-Hikmah.